THE ROLE OF TRADITIONAL ISLAM IN THE DEVELOPMENT OF SPIRITUAL VALUES - Shodibek Mekhmonaliyev (Bright Mind Publishing, 2025)
This article analyzes the role of Islam, particularly the traditional Hanafi school and Maturidi theological doctrine, in the historical formation and development of the spiritual values of the Uzbek people. The article explores the relevance of this religious and spiritual heritage in preserving national identity and ensuring moral stability in the context of globalization. It also discusses the negative influence of foreign religious movements and the importance of collective responsibility and public oversight in modern society.
Keywords: Spiritual values, traditional Islam, Hanafi madhhab, Maturidism, society, globalization, national identity, social stability.